Mejoramiento del proceso de fabricación de paneles de refrigeración para reducir las pérdidas productivas en la empresa “Ecuatoriana de Refrigeración S.A”. - Herrera Tigselema, Germánico Omar (2021)
The research project aims to improve the panel manufacturing process to reduce production losses in a company dedicated to this type of product. Initially, the characteristics of the company are identified and the current situation of its processes, which are cutting, rolling, pressing and storage, is analyzed. Through material-based flowcharts and analytically, the activities necessary for the manufacture of cooling panels are observed and recorded. In addition, the route diagram is made in which a total of 20 activities are identified, which are executed around the plant until reaching the finished product warehouse. Subsequently, with a study of times and movements in which 15 samples are taken for each activity, the supplements are obtained and the standard times for each process are calculated. In this study, it is found that the bottleneck process is pressing with a time of 23.03 minutes/panel, which sets the production rate, so initially the theoretical output of panels is 19 and the real output for efficiency is 18. Finally, an improvement plan is proposed with which a proposed time study is carried out and improvements are obtained at the level of productivity and efficiency in the manufacture of panels. The results show that the cycle time decreases by 1.87%; it goes to 22.60 minutes/panel which increases the production capacity by 1.90% since 20 panels can be manufactured.